2014
DOI: 10.1002/ejoc.201402260
|View full text |Cite
|
Sign up to set email alerts
|

Neighbouring Group Participation During Glycosylation: Do 2‐Substituted Ethyl Ethers Participate?

Abstract: The development of new protecting groups that undergo neighbouring group participation (NGP) via six‐membered ring intermediates to promote the formation of α‐1,2‐cis glycosidic linkages complements the established use of 5‐ring NGP in terms of stereochemical outcome. A selection of glycosyl donors was synthesised that possessed novel 2‐iodo‐ and 2‐(phenylseleno)ethyl ether protecting groups in an attempt to promote highly α‐selective glycosylation by 6‐ring NGP. Although the fully armed donors produced α‐gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…The excellent cis -selectivity observed in this kinetic ring closure contrasts with the thermodynamic trans -selectivity seen on ring closure of 2- O -(2-thioethyl)glucopyranosyl cations and related systems to hetero-bicyclo[4.4.0]decane-like systems, which are governed by the steric factors in the product. 129131 The preference of the tricyclic glucose derivative 32 for the 1 S 5 conformation of the pyranose ring as opposed to the 4 C 1 chair must arise because of a combination two unfavorable steric interactions in the chair: the 1,3-diaxial interaction between the axial anomeric CC bond and the axial C3-H3 bond and the gauche butane interaction emphasized in red in Scheme 8. This is because simple 4,6- O -benzylidene protected α- C -glucopyranosides, with an axial substituent at C1 but lacking the third ring, exist predominantly as 4 C 1 conformers (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…The excellent cis -selectivity observed in this kinetic ring closure contrasts with the thermodynamic trans -selectivity seen on ring closure of 2- O -(2-thioethyl)glucopyranosyl cations and related systems to hetero-bicyclo[4.4.0]decane-like systems, which are governed by the steric factors in the product. 129131 The preference of the tricyclic glucose derivative 32 for the 1 S 5 conformation of the pyranose ring as opposed to the 4 C 1 chair must arise because of a combination two unfavorable steric interactions in the chair: the 1,3-diaxial interaction between the axial anomeric CC bond and the axial C3-H3 bond and the gauche butane interaction emphasized in red in Scheme 8. This is because simple 4,6- O -benzylidene protected α- C -glucopyranosides, with an axial substituent at C1 but lacking the third ring, exist predominantly as 4 C 1 conformers (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…The oxygen-containing auxiliary of 2S and 2R was expected to be a less efficient neighboring group participant compared to the thiophenyl-containing derivative. 19 Finally, glycosyl donors 3S and 3R having chiral C-2 moieties at C-2 are derived from 1S and 1R and cannot participate because of a lack of a heteroatom at the C-2′ position. It was found that the nature of the heteroatom of the auxiliary greatly influenced the anomeric outcome of the glycosylations and only the use of glycosyl donor 1S gave consistently α -anomeric products.…”
Section: Introductionmentioning
confidence: 99%
“…15,17 Analogous six-membered selenonium ions have also been characterized by NMR at low temperature and used as glycosyl donors. 20 Differences in the composition of product mixtures arising from the activation of 5 and 6 in the presence of isopropanol, with only 6 affording any isopropyl glycosides, are best explained by the change in the protection at the 4- and 6-positions. It is widely appreciated that the 4,6- O -benzylidene acetal group is more disarming than two correspondingly located benzyl ethers owing to a combination of torsional and electronic effects.…”
Section: Resultsmentioning
confidence: 99%